One step densification of SDC-Na2CO3 nano-composite electrolytes for SOFC applications by cold sintering process - Murutoglu, Murat; Gultekin, Aygul Alkan; Gunhan, Busra; Ucun, Tugce; Büyükaksoy, Aligül; Ozsarac, Ugur; Yılmaz, Hüseyin (Wiley, 2023)
Sm0.2Ce0.8O1.9- 30% Na2CO3 (Sm doped ceria (SDC)-30N) nano-composite electrolytes were densified in a single step via cold sintering process (CSP). At 200 & DEG;C and 450 MPa of uniaxial pressure, samples up to 97% of their theoretical density could be obtained. The effect of processing parameters, such as temperature, uniaxial pressure, processing duration, and moisture content, on the densification of the nano-composite electrolytes was investigated. The thermal, microstructural, and electrical properties of nano-composites were investigated by differential scanning calorimetry, X-ray diffractometer, scanning electron microscope, and EIS analysis. SDC crystallite sizes were found to be around 25 nm, barely coarsened after CSP by which the true nano nature of the nano-composite could be preserved. Because, by conventional processing high density values could not be attained and high processing temperatures in excess of 600 & DEG;C had to be used, promoting particle coarsening. The highest total electrical conductivity was found to be 2.2 x 10(-2) S cm(-1) at 600 & DEG;C, with an activation energy of 0.83 eV for SDC-30N nano-composites. The present investigation revealed that the implementation of cold sintering technique resulted in significant enhancements in the densification of nano-composite electrolytes, thereby rendering them suitable for efficient utilization in SOFC applications, as compared to the conventional production methods.
Keywords: ceria-carbonate; cold sintering; nanocomposites; solid oxide fuel cells